The Complexity in Managing Acute Heart Failure Patients in Intensive Cardiac Care Unit - Waranugraha, Yoga (Universitas Brawijaya, 2023)
Acute heart failure (AHF) is characterized by sudden or gradual onset of heart failure. AHF patients face the possibility of mortality, not only due to cardiovascular causes but also due to the complications arising from organ dysfunction caused by inadequate perfusion or the presence of organ congestion. It is frequent for patients with AHF to require treatment in the intensive cardiac care unit (ICCU). In this article, we are discussing and summarizing the current AHF treatment strategy in ICCU.